Income risk, precautionary saving, and loss aversion: An empirical test - Marcela Ibanez; Sebastian O. Schneider (Max Planck Institute for Research on Collective Goods, 2021)
This paper empirically examines the behavioral precautionary saving hypothesis by Koszegi and Rabin (2009) stating that uncertainty about future income triggers saving because of loss aversion. We extend their theoretical analysis to also consider the internal margin, i.e., the strength, of loss aversion, and empirically study the relation between income risk, experimentally elicited loss aversion and precautionary savings. We do so using a sample of 640 individuals from the low-income population of Bogotá, characterized by limited financial education and subject to substantial income risk. In line with the theoretical predictions, we find that an increase in income risk is associated with higher savings for loss-averse individuals, and that this increase in savings grows with the degree of loss aversion. Thus, as suggested by Koszegi and Rabin (2009), but contrarily to common assumptions, our findings establish that loss aversion is not necessarily an obstacle to saving, and thus identify new approaches of increasing saving among individuals with low financial education.
hdl:21.11116/0000-0008-1716-6
Keywords: D11; D14; D15; D81; D90; G40; J65; O16; 330; Reference-dependent utility; expectations; consumption plans; precautionary savings; loss aversion; risk preferences; income risk; low-income; Bogotá; experiment